[latex] (x^{2}+5x) ^{2} -4( x^{2} +5x)-12=0[/latex]

[latex] (x^{2}+5x) ^{2} -4( x^{2} +5x)-12=0[/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex] (x^{2}+5x) ^{2} -4( x^{2} +5x)-12=0 \\ x^{2} +5x=t \\ t^2-4t-12=0 \\ [/latex] [latex]t_1+t_2=4 \\ t_1t_2= -12[/latex] - теорема Виета [latex]t_1=6 \\ t_2=-2[/latex] [latex] x^{2} +5x=t[/latex] [latex] \\x^{2} +5x=6 \\ x^{2} +5x-6 =0 \\ x_1+x_2= -5 \\ x_1x_2=-6 \\ x_1=-6 \\ x_2=1 \\ \\ \\ x^{2} +5x=-2 \\ x^{2} +5x+2 =0\\ x= \frac{-5б \sqrt{5^2-4*2} }{2*1} \\ x= \frac{-5б \sqrt{25-8} }{2} \\ x= \frac{-5б \sqrt{17} }{2} \\[/latex] Ответ: x₁=-6, x₂=1, x₃ = (-5-√17)/2, x₄= (-5+√17)/2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы